Standalone ECG monitoring system using digital signal processing hardware - Goh, Chun Seng (2012)
This paper describes the implementation of low cost standalone Digital Signal Processing (DSP) hardware for ECG monitoring in order to assist physician or cardiologist to carry out their visual observation in ECG monitoring. The visual observation is in real time, where the acquired ECG from the subject can be seen on the graphic LCD and it is important to ensure the signal is stable and consistent before the pre-recording session take place which would help the cardiologist’s or physician’s in analysis and diagnosis, accurately. The design of the DSP hardware based stand alone system are divided into three hardware units, first the digital signal processor with memory unit, second is the signal monitoring displays unit and third is analog front end unit. Firmware development in this system design is to attach each hardware unit to perform specific functions in carrying out operation on the stand alone system. The advantages of this system are the ability to run in stand-alone operation and as well as eligibility of updating on board pre-program algorithm for ECG analysis which existing ECG monitoring equipment are lacking, which means that this stand alone system could be programmed to suit a particular need.